Relationships Between Components of Blood Pressure and Cardiovascular Events in Patients with Stable Coronary Artery Disease and Hypertension. Issue 1 (January 2018) - Vidal-Petiot, Emmanuelle; Greenlaw, Nicola; Ford, Ian; Ferrari, Roberto; Fox, Kim M.; Tardif, Jean-Claude; Tendera, Michal; Parkhomenko, Alexander; Bhatt, Deepak L.; Steg, P. Gabriel
Abstract : Observational studies have shown a J-shaped relationship between diastolic blood pressure (BP) and cardiovascular events in hypertensive patients with coronary artery disease. We investigated whether the increased risk associated with low diastolic BP reflects elevated pulse pressure (PP). In 22 672 hypertensive patients with coronary artery disease from the CLARIFY registry (Prospective Observational Longitudinal Registry of Patients With Stable Coronary Artery Disease), followed for a median of 5.0 years, BP was measured annually and averaged. The relationships between PP and diastolic BP, alone or combined, and the primary composite outcome (cardiovascular death or myocardial infarction) were analyzed using multivariable Cox proportional hazards models. Adjusted hazard ratios for the primary outcome were 1.62 (95% confidence interval [CI], 1.40–1.87), 1.00 (ref), 1.07 (95% CI, 0.94–1.21), 1.54 (95% CI, 1.32–1.79), and 2.34 (95% CI, 1.95–2.81) for PP<45, 45 to 54 (reference), 55 to 64, 65 to 74, and ≥75 mm Hg, respectively, and 1.50 (95% CI, 1.31–1.72), 1.00 (reference), and 1.58 (95% CI, 1.42–1.77) for diastolic BPs of <70, 70 to 79 (ref), and ≥80 mm Hg, respectively. In a cross-classification analysis between diastolic BP and PP, the relationship between diastolic BP and the primary outcome remained J-shaped when the analysis was restricted to patients with the lowest-risk PP (45–64 mm Hg), with adjusted hazard ratios of 1.53 (95% CI, 1.27–1.83), 1.00 (ref), and 1.54 (95% CI, 1.34–1.75) in the <70, 70 to 79 (reference), and ≥80 mm Hg subgroups, respectively. The J-shaped relationship between diastolic BP and cardiovascular events in hypertensive patients with coronary artery disease persists in patients within the lowest-risk PP range and is therefore unlikely to be solely the consequence of an increased PP reflecting advanced vascular disease. Clinical Trial Registration—: URL:http://www.clarify-registry.com . Unique identifier: ISRCTN43070564. Abstract : Supplemental Digital Content is available in the text.